2020
DOI: 10.1513/annalsats.201905-378oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Positive Airway Pressure on Vascular Function and Cardiac Structure in Diabetes and Sleep Apnea. A Randomized Controlled Trial

Abstract: Rationale: Although both type 2 diabetes mellitus (T2DM) and obstructive sleep apnea (OSA) are independently recognized as risk factors for cardiovascular disease, little is known about their interaction.Objectives: We hypothesized that T2DM and OSA act synergistically to increase vascular risk, and that treatment of OSA would improve vascular reactivity in patients with T2DM plus OSA.Methods: Cross-sectional study of 141 adults with T2DM, OSA, T2DM plus OSA, and control subjects, followed by a 3-month, parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Of 3300 articles recognized by the initial search, 253 were retrieved for more detailed assessment, and seven articles 7,14,20–24 were included in the meta‐analysis (Figure 1). Baseline characteristics of trials included in the meta‐analysis are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of 3300 articles recognized by the initial search, 253 were retrieved for more detailed assessment, and seven articles 7,14,20–24 were included in the meta‐analysis (Figure 1). Baseline characteristics of trials included in the meta‐analysis are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among men 40 to 70 years old, those with AHI > or = 30 were 68% more prone to develop coronary artery disease than those with AHI < 5 [ 60 ]. Bakker et al study showed that the 3 months of CPAP therapy resulted in lowering the left ventricle (LV) end-diastolic volume, as assessed by the magnetic resonance imaging (MRI) [ 61 ]. Conversely, in another study no significant changes were noted in ventricular dimensions, systolic and diastolic function, valvular function and coronary vasodilation to nitroglycerin after 3 months of CPAP.…”
Section: Endothelial Function After Treatment With Cpap In Specific Subgroupsmentioning
confidence: 99%
“…Lifestyle intervention and successful weight reduction significantly improved AHI, BMI, serum triglycerides and insulin resistance in mild OSA patients [ 64 ]. The CPAP effect on improving endothelial function measured by the FMD is even greater in OSA patients with coexisting diabetes [ 61 ]. The treatment efficiency in coexisting diabetes and OSA could be explained by common mechanisms leading to endothelial dysfunction, which comprises ROS overproduction.…”
Section: Endothelial Function After Treatment With Cpap In Specific Subgroupsmentioning
confidence: 99%
“…These randomized clinical trials showing no beneficial effect of CPAP on overall cardiovascular events in moderate‐to‐severe OSA excluded severely sleepy patients. Thus, it remains unknown whether in the excessively sleepy OSA phenotype a beneficial effect on cardiovascular outcomes might have been observed . Ongoing efforts to understand OSA mechanisms may also help to develop personalized therapy for OSA and to improve clinical trial design.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%